Best Answer

You solve it like this: 7x=4x-6 (subtract 4x from both sides)

3x=-6 (divide both sides by 3)

x=-2

Q: 7x equals 4 x - 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

7x + 2 = -4 7x + 2 - 2 = -4 - 2 7x = -6 7x/7 = -6/7 x = -6/7

x=6

hujkImproved anwser:2x+6 = 7x-42x-7x = -4-6-5x = -10x = 2

7x - 4 = 60 7x = 64 x = 9.14

x=6 hope this helps

Related questions

7x-4=x+2 7x=x+2+4 7x=x+6 7x-x=6 6x=6 X=1

7x + 2 = -4 7x + 2 - 2 = -4 - 2 7x = -6 7x/7 = -6/7 x = -6/7

6 = 7x + x First, add 7x and x.6 = 8xNow, divide both sides by 8.6/8 = xSimplify the answer.3/4 = x.

x=6

hujkImproved anwser:2x+6 = 7x-42x-7x = -4-6-5x = -10x = 2

7x = 6 x = 6/7

9x-4 = 7x+8 9x-7x = 8+4 2x = 12 x = 6

7x - 4 = 60 7x = 64 x = 9.14

x=6 hope this helps

x = -4

7x-3=39 7x=42 x=6

7x + 6 = -18 7x = -24 x = -24/7 x = -3.428571 recurring (that is, -3.428571428571...)